Selective methylation of kaempferol via benzylation and deacetylation of kaempferol acetates - Mei, Qinggang; Wang, Chun; Yuan, Weicheng; Zhang, Guolin (Beilstein Journal of Organic Chemistry, 2015)
A strategy for selective mono-, di- and tri-O-methylation of kaempferol, predominantly on the basis of selective benzylation and controllable deacetylation of kaempferol acetates, was developed. From the selective deacetylation and benzylation of kaempferol tetraacetate (1), 3,4′,5,-tri-O-acetylkaempferol (2) and 7-O-benzyl-3,4′5,-tri-O-acetylkaempferol (8) were obtained, respectively. By controllable deacetylation and followed selective or direct methylation of these two intermediates, eight O-methylated kaempferols were prepared with 51–77% total yields from kaempferol.
Keywords: benzylation; deacetylation; kaempferol; methylation; regioselectivity

(untitled) - Veitch, N. C.; Grayer, R. J. (Nat. Prod. Rep., 2011)

(untitled) - Park, J. S.; Rho, H. S.; Kim, D. H.; Chang, I. S. (J. Agric. Food Chem., 2006)

(untitled) - Calderon-Montano, J. M.; Burgos-Moron, E.; Perez-Guerrero, C.; Lopez-Lazaro, M. (Mini-Rev. Med. Chem., 2011)

(untitled) - Chen, A. Y.; Chen, Y. C. (Food Chem., 2013)

(untitled) - Somerset, S. M.; Johannot, L. (Nutr. Cancer, 2008)

(untitled) - Chen, H.-J.; Chung, C.-P.; Chiang, W.; Lin, Y.-L. (Food Chem., 2011)

(untitled) - Al-Dabbas, M. M.; Kitahara, K.; Suganuma, T.; Hashimoto, F.; Tadera, K. (Biosci., Biotechnol., Biochem., 2006)

(untitled) - De Meyer, N.; Haemers, A.; Mishra, L.; Pandey, H.-K.; Pieters, L. A. C.; Berghe, D. A. V.; Vlietinck, A. J. (J. Med. Chem., 1991)

(untitled) - Wang, Y.; Hamburger, M.; Gueho, J.; Hostettmann, K. (Phytochemistry, 1989)

(untitled) - Park, C. H.; Kim, K. H.; Lee, I. K.; Lee, S. Y.; Choi, S. U.; Lee, J. H.; Lee, K. R. (Arch. Pharmacal Res., 2011)

(untitled) - Okada, Y.; Miyauchi, N.; Suzuki, K.; Kobayashi, T.; Tsutsui, C.; Mayuzumi, K.; Nishibe, S.; Okuyama, T. (Chem. Pharm. Bull., 1995)

(untitled) - Jiang, H.; Hu, J. R.; Zhan, W. Q.; Liu, X. (Nat. Prod. Res., 2009)

(untitled) - Tu, Y.-C.; Lian, T.-W.; Yen, J.-H.; Chen, Z.-T.; Wu, M.-J. (J. Agric. Food Chem., 2007)

(untitled) - Ram, S. N.; Dwivedi, S. P. D.; Pandey, V. B.; Rao, Y. V. (Fitoterapia, 1989)

(untitled) - Hattori, H.; Okuda, K.; Murase, T.; Shigetsura, Y.; Narise, K.; Semenza, G. L.; Nagasawa, H. (Bioorg. Med. Chem., 2011)

(untitled) - Kuntz, S.; Wenzel, U.; Daniel, H. (Eur. J. Nutr., 1999)

(untitled) - Beutler, J. A.; Hamel, E.; Vlietinck, A. J.; Haemers, A.; Rajan, P.; Roitman, J. N.; Cardellina, J. H., II; Boyd, M. R. (J. Med. Chem., 1998)

(untitled) - Kim, B.-G.; Jung, B.-R.; Lee, Y.; Hur, H.-G.; Lim, Y.; Ahn, J.-H. (J. Agric. Food Chem., 2006)

(untitled) - Bouktaib, M.; Lebrun, S.; Atmani, A.; Rolando, C. (Tetrahedron, 2002)

(untitled) - Zhou, Z.-h.; Fang, Z.; Jin, H.; Chen, Y.; He, L. (Synthesis, 2010)

(untitled) - Mu, G.; Pu, W.; Zhou, M.; Liu, Y.; Yang, H.; Wang, C. (Chin. J. Org. Chem., 2013)

(untitled) - Wang, X.; Lü, G.; Yang, L.-J.; Wang, F.; Wang, C. (Chin. J. Org. Chem., 2011)

(untitled) - Rao, K. V.; Owoyale, J. A. (J. Heterocycl. Chem., 1976)

(untitled) - Li, N. G.; Shi, Z. H.; Tang, Y. P.; Yang, J. P.; Lu, T. L.; Zhang, F.; Huang, Y. W.; Wang, Z. J.; Duan, J. A. (Chin. Chem. Lett., 2011)

(untitled) - Jurd, L. (J. Am. Chem. Soc., 1958)

(untitled) - Kawamura, T.; Hayashi, M.; Mukai, R.; Terao, J.; Nemoto, H. (Synthesis, 2014)

(untitled) - Wu, Z.; Cai, S.; Fan, W.; Wang, Q. (Chin. J. Org. Chem., 2012)

(untitled) - Scio, E.; Ribeiro, A.; Alves, T. M. A.; Romanha, A. J.; Dias de Souza Filho, J.; Cordell, G. A.; Zani, C. L. (Phytochemistry, 2003)

(untitled) - Jurd, L. (J. Org. Chem., 1962)